2015
DOI: 10.1111/jdi.12406
|View full text |Cite
|
Sign up to set email alerts
|

Important role of 5‐hydroxytryptamine in glucocorticoid‐induced insulin resistance in liver and intra‐abdominal adipose tissue of rats

et al.

Abstract: Aim/IntroductionBoth glucocorticoids and 5‐hydroxytryptamine (5‐HT) have been shown to induce insulin resistance (IR) in hepatocytes and adipocytes. Here, we explore whether there is a correlation between them.Materials and MethodsExcept for the control group, male rats were exposed to dexamethasone treated with or without para‐chlorophenylalanine (pCPA), or carbidopa for 20 days. Except for the control group, buffalo rat liver 3A (BRL‐3A) cells were exposed to dexamethasone for 24 h, treated with or without p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…To examine whether 5‐HT is synthesized and is influenced by Dex in the liver, visceral adipose and skeletal muscle tissue of rats, we assessed Tph1 and AADC expression by western blot, and 5‐HT levels in these three tissues and serum. In agreement with a previous study, the expressions of Tph1 and AADC (Figure a,b) were detected in the liver and visceral adipose tissues, but were not detected in the skeletal muscle (data not shown), whereas rats' chronic exposure to Dex showed markedly upregulated Tph1 and AADC expression in both tissues. Accordingly, 5‐HT levels in the serum and three tissues (Figure d) were increased significantly by Dex, which were inhibited by CDP in a dose‐dependent manner in the CDP or Sar and CDP co‐treatment rats, whereas Sar alone did not obviously change 5‐HT levels in the serum or in the three tissues.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…To examine whether 5‐HT is synthesized and is influenced by Dex in the liver, visceral adipose and skeletal muscle tissue of rats, we assessed Tph1 and AADC expression by western blot, and 5‐HT levels in these three tissues and serum. In agreement with a previous study, the expressions of Tph1 and AADC (Figure a,b) were detected in the liver and visceral adipose tissues, but were not detected in the skeletal muscle (data not shown), whereas rats' chronic exposure to Dex showed markedly upregulated Tph1 and AADC expression in both tissues. Accordingly, 5‐HT levels in the serum and three tissues (Figure d) were increased significantly by Dex, which were inhibited by CDP in a dose‐dependent manner in the CDP or Sar and CDP co‐treatment rats, whereas Sar alone did not obviously change 5‐HT levels in the serum or in the three tissues.…”
Section: Resultssupporting
confidence: 93%
“…Dex-induced production of 5-HT in the entero-chromaffin cells has been observed in the small intestine, especially in the duodenum of rats 51 . However, both our previous study 22 and present study found that 5-HT is also synthesized in the liver and visceral adipose tissues, which were upregulated by Dex with upregulated expressions of both Tph1 and AADC, and that increased 5-HT levels by Dex in both tissues came from tissue itself rather than the blood. 5-HT by acting on 5-HT 2A R mediates hepatic steatosis and IR has been shown in several studies 24,52 , whereas activation of the mTOR-S6K pathway has been shown to be the mechanism of 5-HT action in the liver 53 , and in the adipocytes and C2C12 myotubes by inhibition of insulin-stimulated activation of the IRS-1-AKT signaling pathway with glucose uptake 54 .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Serotonin binds to mechanistic target of rapamycin (mTOR), increasing liver lipogenesis and impairing insulin signaling in adipocytes. Accordingly, inhibition of serotonin degradation by monoamine oxidase A (MAOA) exacerbates the effects (110). Compounding the problem, serotonin has well-documented effects on brain-mediated control of appetite.…”
Section: Diabetesmentioning
confidence: 99%
“…Therefore, the stability of frequently-used reference genes is relative. From a survey of different studies of adipose tissue, qRT-PCR data were normalized to different reference genes, such as Glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) [13], β-actin [14], 18S [15] and acidic ribosomal phosphoprotein P0 ( 36B4 ) [16]. However, no research has studied the stability of frequently-used reference genes in different types of rat adipose tissue.…”
Section: Introductionmentioning
confidence: 99%